2018
DOI: 10.1515/joc-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of an all optical 8 to 3 binary encoder based on optimized photonic crystal OR gates

Abstract: The most recently developed optical encoders are based on non-linear Kerr effect which require high input power. Here, we report 8 to 3 optical binary encoder based on linear effects which greatly reduces the input power requirement. The proposed encoder consists of three optical 4-input port OR gates and an optical buffer gate. Simulation results have proved correct operation states of the encoder and numerical analysis is done in order to additional evaluation. The maximum switching delay and total footprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Several combinational and sequential logic circuits for applications such as switching, multiplexing, parity checking, encoding, filtering and so on are constructed using logic gates [4]. All these circuits can be implemented using optical logic gates without any electro-optic conversions [5] [6] [7] [8] [9]. Several methods have been utilized to implement these gates such as using non-linear ring resonators [10], Semiconductor Optical Amplifiers (SOA) [11], non-linear directional couplers [12], Highly Non-Linear Fibers [13], photonic crystals [14], plasmonic slot waveguides [15] and quantum dot SOA [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several combinational and sequential logic circuits for applications such as switching, multiplexing, parity checking, encoding, filtering and so on are constructed using logic gates [4]. All these circuits can be implemented using optical logic gates without any electro-optic conversions [5] [6] [7] [8] [9]. Several methods have been utilized to implement these gates such as using non-linear ring resonators [10], Semiconductor Optical Amplifiers (SOA) [11], non-linear directional couplers [12], Highly Non-Linear Fibers [13], photonic crystals [14], plasmonic slot waveguides [15] and quantum dot SOA [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are more popular among designers. A large number of parameters, including the radius of the dielectric rod, the lattice constant, the type of rod arrangement, the dielectric constant, and the PhC unit cells' position, affect the resonant's intensity and frequency modes [14][15][16][17][18][19]. By changing every parameter, the blue or redshift occurs at resonant modes.…”
Section: Introductionmentioning
confidence: 99%
“…Photonic crystal ring resonators (PCRR) are well-known structures because they have excellent characteristics in realizing various compact optical devices [21][22][23][24][25]. Resonant modes of a PCRR depends on several physical parameters such as rod radius, lattice constant, and rods' refractive index [26][27][28][29][30][31]. In recent reports, researchers have shown that a PCRR can be used as an optical filter, and blueshift or redshift may occur in the resonant mod by changing any of these parameters [13,23].…”
Section: Introductionmentioning
confidence: 99%